2021
DOI: 10.1089/jmf.2020.4750
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Polysaccharides Attenuate Ovalbumin-Induced Allergic Rhinitis in Rats by Inhibiting NLRP3 Inflammasome Activation and NOD2-Mediated NF-κB Activation

Abstract: Allergic rhinitis (AR) is an IgE-mediated chronic inflammatory disease of the allergic nasal mucosa. It has a significant effect on quality life; most patients with AR also suffer from sleep disorders, mood disorders, and deterioration in social relationships. As increasing numbers of medicinal plants show productive anti-inflammatory activity against inflammatory diseases, there is growing interest in natural medicinal plant ingredients. To this end, we selected Astragalus polysaccharides (APS) to evaluate it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…Several papers highlighted the anti-inflammatory activity of different polysaccharides probably ascribed to NLRP3 inhibition by decreased protein levels of NLRP3, ASC, caspase-1, and IL-1β [ 172 , 173 , 174 ]; however, few works assessed the pro-inflammatory efficacy of some polysaccharides towards the NLRP3 inflammasome. In particular, Liu et al found out that the polysaccharide SF-2, a mannoglucan sulfate isolated from starfish ( A. rollestoni ), could improve the release of cytokines and the expression of NLRP3 in primary macrophages, confirmed by the elevated expression of NLRP3, cleaved caspase-1, and ASC proteins [ 131 ].…”
Section: Food Components As Nlpr3 Modulatorsmentioning
confidence: 99%
“…Several papers highlighted the anti-inflammatory activity of different polysaccharides probably ascribed to NLRP3 inhibition by decreased protein levels of NLRP3, ASC, caspase-1, and IL-1β [ 172 , 173 , 174 ]; however, few works assessed the pro-inflammatory efficacy of some polysaccharides towards the NLRP3 inflammasome. In particular, Liu et al found out that the polysaccharide SF-2, a mannoglucan sulfate isolated from starfish ( A. rollestoni ), could improve the release of cytokines and the expression of NLRP3 in primary macrophages, confirmed by the elevated expression of NLRP3, cleaved caspase-1, and ASC proteins [ 131 ].…”
Section: Food Components As Nlpr3 Modulatorsmentioning
confidence: 99%
“…Serum levels of these inflammatory mediators are usually increased in obese patients with NAFLD and the obese Zucker rat model, as reported in the studies by Hakkak et al ( 29 ) and Kozaczek et al ( 30 ). We also reported how feeding SPI reduces the expression of inflammation-related genes, such as IL-33 and IL-1B, that could be helping in the general reduction of liver steatosis observed with the SPI diet ( 31 ). In humans, studies have described a reduction in the expression of CYP3A family related to liver inflammation ( 76 ), and a study by Woolsey et al ( 77 ) reported a reduction of CYP3A family in humans and a murine model for NAFLD.…”
Section: Discussionmentioning
confidence: 93%
“…We can extrapolate both the short- and long-term results to adolescents and adults, respectively. Recently, we reported that SPI had a protective effect against liver steatosis ( 29 ) and proposed that SPI reduces inflammation and enhances the lipid transport out of the liver in obese Zucker rats ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of pro-inflammatory cytokines TNF-α and IL-1β were also increased by LPS treatment but decreased by AGS treatment in a dose dependent manner. Previous studies have shown that the expression of inflammatory proteins and pro-inflammatory cytokines is mediated by the NF-κB signaling pathway [34,35]. When an inflammatory reaction occurs in a cell, the inhibitory protein IκBα is phosphorylated to release NF-κB, which then undergoes nuclear transfer to regulate the expression of various inflammation-related genes such as cytokines, iNOS and COX-2 [36].…”
Section: Discussionmentioning
confidence: 99%